Pengembangan Buku Ajar Guru Berbasis Pendekatan Saintifik pada Mata Pelajaran Humas dan Keprotokolan Semester Gasal Kelas XI OTKP di SMK YPM 5 Sukodono - Indah Tia Pratiwi; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This development research was carried out with the aim to find out the process of developing teacher textbooks, the feasibility of teacher textbooks, and teacher responses to teacher textbooks based on a scientific approach to public relations subjects and protocol of odd semester XI OTKP at SMK YPM 5 Sukodono. The development model applied in this study is 4-D which consists of the defining stage, the design phase, the development phase, and the disseminate stage. The research instruments used included study sheets and validation of material experts, linguists, and graphic experts as well as teacher response questionnaire sheets using a rating scale that is the Likert scale. The results showed that the results of the assessment of the feasibility of teacher's textbooks from material experts amounted to 87.5% with a very strong category, the assessment of linguists amounted to 78.2% with a strong category, and the assessment of the graphic experts amounted to 98.2% with a very strong category. From the results of the validation obtained an average value of 88% in the category of interpretation is very strong, and the teacher's response of 81.87% in the category of interpretation is very strong. Based on the results of the study it can be concluded that the teaching textbooks are based on a scientific approach to the subjects of public relations and protocol protocol odd semester XI OTKP at SMK YPM 5 Sukodono declared worthy to be used as teaching material.